2021
DOI: 10.1002/eap.2473
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the evolution of herbicide resistance in weed species with a complex life cycle

Abstract: A growing number of weed species have evolved resistance to herbicides in recent years, which causes an immense financial burden to farmers. An increasingly popular method of weed control is the adoption of crops that are resistant to specific herbicides, which allows farmers to apply the herbicide during the growing season without harming the crop. If such crops are planted in the presence of closely related weed species, it is possible that resistance genes could transfer from the crop species to feral popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…However, then the effect reverses, delaying resistance evolution. This effect is observed for diploids and tetraploid perennials (Holmes et al 2022).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, then the effect reverses, delaying resistance evolution. This effect is observed for diploids and tetraploid perennials (Holmes et al 2022).…”
Section: Discussionmentioning
confidence: 80%
“…Liu et al (2019) presented an individual-based model, which captures the sexual reproduction, including self-pollination, but lacks a seed bank. The density-dependent discrete model of Holmes et al (2022) comprises both, a seed bank and a bank of rhizome buds. However, it lacks the possibility of de novo resistance evolution, and pure outcrossing is assumed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wide flowering windows in johnsongrass were also reported in California 45 , Kansas, Missouri, and Nebraska 44 , which corroborates our observations. The high degree of flowering synchrony allows for natural outcrossing among members of Sorghum genera and accelerates the dispersal of resistance-conferring alleles and other novel traits 3 , 9 , 15 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Coupled with the excessive use of herbicides, the herbicide-resistant weeds in farmland are increasing year by year (Buddenhagen et al, 2021;Green and Siehl, 2021;Holmes et al, 2022). Previous researches have shown that the ptxD/Phi system effectively control weeds in cotton and tobaccos (Lopez-Arredondo and Herrera-Estrella, 2012; Pandeya et al, 2018), but the application of this system in rapeseed has not been reported.…”
Section: Discussionmentioning
confidence: 99%